2017
DOI: 10.1007/s00018-017-2463-7
|View full text |Cite
|
Sign up to set email alerts
|

Clearance of cerebral Aβ in Alzheimer’s disease: reassessing the role of microglia and monocytes

Abstract: Deficiency in cerebral amyloid β-protein (Aβ) clearance is implicated in the pathogenesis of the common late-onset forms of Alzheimer’s disease (AD). Accumulation of misfolded Aβ in the brain is believed to be a net result of imbalance between its production and removal. This in turn may trigger neuroinflammation, progressive synaptic loss, and ultimately cognitive decline. Clearance of cerebral Aβ is a complex process mediated by various systems and cell types, including vascular transport across the blood–br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
181
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 221 publications
(187 citation statements)
references
References 400 publications
(523 reference statements)
3
181
0
3
Order By: Relevance
“…In addition to the effect seen on MMP‐9, we also found that resveratrol may facilitate the activation of microglia/macrophages, thereby inducing long‐term adaptive immunity that may be clinically beneficial . Since chronic neuroinflammation likely contributes to the focal encephalopathy causing clinical dementia, activation of specific microglia/macrophages may be neuroprotective . As AD progresses, innate immune cells, such as resident microglia and macrophages, exhibit dysfunctional or senescent profiles characterized by impaired phagocytosis.…”
Section: Resveratrol For the Treatment Of Alzheimer's Diseasementioning
confidence: 99%
“…In addition to the effect seen on MMP‐9, we also found that resveratrol may facilitate the activation of microglia/macrophages, thereby inducing long‐term adaptive immunity that may be clinically beneficial . Since chronic neuroinflammation likely contributes to the focal encephalopathy causing clinical dementia, activation of specific microglia/macrophages may be neuroprotective . As AD progresses, innate immune cells, such as resident microglia and macrophages, exhibit dysfunctional or senescent profiles characterized by impaired phagocytosis.…”
Section: Resveratrol For the Treatment Of Alzheimer's Diseasementioning
confidence: 99%
“…A large body of experimental evidence supports the view that amyloid plaques are (Taylor et al, ) key to driving AD pathogenesis through activation of both the innate and the adaptive immune pathways (Hardy & Selkoe, ). The ensuing neuroinflammatory response sustains the production and release of neurotoxic and inflammatory mediators (Schwartz & Deczkowska, ; Su, Bai, & Zhang, ) through the activation of microglia and astrocytes, causing neuronal cell death (Meda et al, ; Zuroff, Daley, Black, & Koronyo‐Hamaoui, ) and the release of inflammatory neurotransmitters and ROS (Tansey, McCoy, & Frank‐Cannon, ).…”
Section: Introductionmentioning
confidence: 99%
“…This data suggests that gal3 is a critical alarmin that amplifies the Aβ-induced proinflammatory response. Since inefficient clearance of Aβ may play a determinant role in AD pathogenesis [76], we analyzed the effect of gal3 in two major mechanisms associated to Aβ clearance: fAβ phagocytosis and IDE-1 levels, a key metalloprotease involved in Aβ degradation by microglia [25,28,39]. Gal3 was able to reduce Aβ phagocytosis, and gal3 deficiency increased IDE-1 levels, suggesting a detrimental role of gal3 in Aβ clearance.…”
Section: Discussionmentioning
confidence: 99%